A new era of cardiac nephroprotection in patients with type 2 diabetes mellitus: the role of Finerenone - I. S. Khalimov; E. A. Polyakova; Yu. A. Shutova (Сахарный диабет)
The main factor in modern healthcare is to increase the length and quality of life of patients, especially with socially significant diseases, such as type 2 diabetes mellitus (T2DM) and its dangerous complication — chronic kidney disease (CKD), associated with a high rate of cardiovascular diseases (CVD), end-stage renal disease and mortality. Effective management of cardiorenal risks in addition with blockers of the renin-angiotensin-aldosterone system and sodium-glucose cotransporter type 2 inhibitors was replenished in 2023 with a new non-steroidal selective mineralocorticoid receptor antagonist — Finerenone. This unique and one-of-a-kind drug improves the control of cellular processes, fibrosis in the kidneys and myocardial remodeling. This review presents the main studies on the mechanism of action of Finerenone, assessment of its effectiveness and safety, and its effect on the risk of developing cardiorenal risk in patients with T2DM. Finerenone is one-of-a-kind drug who has no alternatives to improve a control of cellular processes, a fibrosis in the kidneys and a myocardial remodeling. In this review we presented Finerenone effects on an eGFR slope as a main kidney function feature, and proposed practice points on safe initiation of the three cardiorenal «pillars» in patients with T2DM in accordance with the current clinical guidelines.